Problematika Pembelajaran Baca Tulis Al-Qur’an Siswa - Rheschy Auliya Kamil; Murniyetti Murniyetti (An-Nuha, 2023)
This research was conducted at SD Negeri 20 Kurao Pagang, Nanggalo, Padang City. This study aims to describe the problems of learning to read and write the Koran for teachers and students. The method used in this research is qualitative. In this study, structured interviews were conducted with research subjects, namely teachers in the field of Islamic religious education, school principals, and fifth-grade students at SD Negeri 20 Kurao Pagang, Nanggalo, Padang City. Collection techniques used are observation, interviews, and documentation. The results of the study show that the problems faced by teachers in learning to read and write the Koran are: 1) Ineffective classroom atmosphere, lack of learning media, and uneven students' ability to recite the Koran; 2) The problems of students in learning to read and write the Koran are lack of ability to recognize hijaiyah letters, not mastering the science of recitation, reading the Koran in Latin script, low student learning motivation.